PEMBAHARUAN HUKUM AGRARIADALAM RANGKA PEMBANGUNAN BERKELANJUTAN - Nurbaedah . (DIVERSI : Jurnal Hukum, 2015)
Sustainable development especially in the field of agrarian law reform in Indonesia is very necessary. To mind the land issue is very urgent and is important to the rule in land regulation of law which is complete. To reduce disputes against former land leasehold, it is necessary to agrarian reform which means a continuous process, thus it requires arrangements related to the allocation, use, authorizing, possessing rights over land that was implemented in order to achieve certainty and legal protection and justice and prosperity for all the people of Indonesia, with the object of former leasehold land, HGB or Rights Management; land affected by the conversion provisions; land submitted voluntarily by its owner, the land rights of the holder violates the law; object land reform; object former land reform; land arise; the land of the former mining area; land donated by the government; exchange of land from and by the government; land purchased by the government; soil release Convertible Production Forest Area, or the land of the former forest area ever released. The purpose of renewal reorganize the inequality of control, ownership, use and exploitation of land, reduce poverty, create job fields, improve people's access to economic resources, especially land, reduce disputes and / or conflicts over land and agrarian, improve and maintain the quality of the environment, and improve food security of community.